Pengaruh Perencanaan Pajak Dan Profitabilitas Terhadap Praktik Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2020 - Shofi Nabila Khoerunnisa; Yeti Apriliawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to examine the effect of tax planning and profitability on earnings management practices. This research method used is quantitative research. The reasearch population in this study used 64 consumer goods sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2020. The sampling technique of this research used purposive sampling method and obtained 34 companies. The independent variable in this study are tax planning (X1) and profitability (X2), while the dependent variable is earnings management (Y). The data analysis technique used is multiple regression analysis with the help of the IBM SPSS 25 application. The research result showed that tax planning has no significant effect on management practices, meanwhile profitability has a significant positive effect on earnings management practices. The result simultaneously showed that tax planning and profitability have a significant effect on earnings management.